Unión de los aceros inoxidables 316L/AL-6XN mediante cinta metálica vítrea base Fe y Ni - Ortega Mondragón, Tania Eréndira (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
In the present study joints of stainless steel AISI 316L and AL-6XN using metallic ribbons glassy Ni and Fe as the joining element were fabricated; joints were conducted at 5, 15 and 30 minutes holding times at a temperature of 820 °C, using an induction furnace. The characterization of both the base materials (stainless steel AISI 316L and AL-6XN) and the joining materials (Fe- and Ni- based metallic glass ribbons) were performed. The amorphous structure of both glassy alloys was verified by X-ray diffraction; through the technique of differential analysis, the melting temperature and crystallization of the tapes was determined, the results showed that for the Ni based ribbon the melting temperature is 1056 °C, meanwhile for the Fe based, was 1137 °C; from this, the joining temperature, was established at 820 °C. For materials, the surface roughness prior the joining process was observed by means of atomic force microscopy, the roughness‟s average were 12.2 and 9.14 nm for the AISI AL-6XN and 316L stainless steels, respectively. The joining experiments were carried out in an assembly sandwich type, by placing the glassy ribbons between the two types of stainless steels. Interfacial characterization was carried out using scanning electron microscopy technique using energy dispersive spectroscopy X-ray for evaluation of the microchemical analyses and observation of the formation of possible compounds. The results show good unions, observing better bonds from 15 minutes, due to a greater diffusion of elements, in addition to a decrease in porosities at the joining interfaces. It was observed that at the joining zones, some phases spreaded through the center of the joints. Nanohardness evaluations performed at the interfaces of the joints were 9.33 GPa and 8.44 GPa, for samples joined with the Fe- and Ni- base glassy alloys, repectivelly. Concerning to the corrosion resistance measured by potentiodynamic polarization tests, carried out in a 3.5 NaCl solution, showed that the corrosion rate (Vcorr) on samples joined with the Fe base glassy ribbon was of 0.029 mm/year, which is almost half (Vcorr=0.062 mm/year) of that obtained for the samples joined with Ni base alloy ribbon.

En el presente estudio se fabricaron las uniones de un acero inoxidable AISI 316L a otro acero inoxidable AISI AL-6XN empleando cintas metálicas vítreas base Ni y base Fe, como elementos de unión; las uniones se llevaron a cabo a 5, 15 y 30 minutos de permanencia a una temperatura de 820 °C utilizando un horno de inducción. Se realizó la caracterización tanto de los materiales base (acero inoxidables AISI 316L y AL-6XN) así como de las cintas metálicas vítreas. Para comprobar y corroborar los datos de los proveedores de los materiales de inicio, se ensayaron muestras de los dos tipos de cintas metálicas vítreas en difracción de rayos X; por medio de la técnica de análisis diferencial se determinó la temperatura de fusión y de cristalización de las cintas, los resultados muestran para la cinta base Ni una temperatura de fusión de 1056 °C y para la base Fe 1137 °C, por cual se estableció una temperatura de unión de 820 °C. Para los materiales, previo a la fabricación de las uniones, a las muestras se les realizó una preparación superficial adecuada para poder implementar la técnica de unión por difusión en estado sólido; inicialmente se cortaron en dimensiones de 10 mm de largo por 5 mm de ancho por 3mm de espesor, y se prepararon las caras de las muestras con desbaste y pulido tradicional. Enseguida se sometieron las muestras a la técnica de microscopía de fuerza atómica para analizar la rugosidad superficial y los resultados muestran rugosidades promedios de 9.14 y 12.2 nm para las muestras de los aceros 316L y AL-6XN, respectivamente. Las uniones se fabricaron mediante un arreglo tipo sándwich empleando como metal de aporte las cintas, la cual se coloca entre los dos materiales base.
Instituto de Investigación en Metalurgia y Materiales. Maestría en Metalurgia y Ciencias de los Materiales
Keywords: info:eu-repo/classification/cti/7; IIMM-M-2015-1597; Aceros inoxidables; Cinta metálica; Vítrea; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5255